A psoriatic arthritis patient who developed hypertriglyceridemia while receiving adalimumab treatment - Mercantepe, Filiz; Topaloğlu, Mehmet Serhat; Yildirim, Murat; Özkaya, Erdem (International Journal of Research in Medical Sciences, 2017)
Anti-TNF agents have prominent effect on inflammatory diseases and they probably have various effects on lipid metabolism. Adalimumab (ADA) is the first fully human TNF-alfa antagonist. Our study presents a male patient who developed evident hypertriglyceridemia while receiving ADA treatment. We retrospectively collected data of one psoriatic arthritis patient treated with adalimumab at the University Hospital of Recep Tayyip Erdogan (November 2016). Adalimumab treatment significantly increased triglyceride from 278mg/dl to 4046mg/dl. The influence of adalimumab treatment on lipid profile seems to be proatherogenic, but further investigation is needed to confirm this hypothesis.